IMPLIKASI MANAJEMEN SUMBER DAYA MANUSIA BERBASIS NILAI NILAI ISLAMI (STUDI PADA BANK MUAMALAT PALOPO) - Muzayyanah Jabani; Tadjuddin Tadjuddin (Institut Agama Islam Negeri Palopo, 2018)
This research analyzes the implication of human resourcrces management based on Islamic values in Bank Muamalat Palopo. The kind of the research is qualitative study. Based on the result of the research, the implication of human resourcrces management based on Islamic values in Bank Muamalat Palopo has involved the Islamic values. It is applied through: a. the recruitment and selection done by considering the result of syariah selection; b. the development of officers is always done by the management of Bank Muamalat and realized in the form of training/workshop; c. the application of working assessment and officers compensation which usually given in the form of reward to the officer who achieves a particular target can improve the officers motivation; d. industrial relation is managed directly by Bank Muamalat central.